Profil Kadar Cholinesterase Darah pada Petani Kelapa Sawit Akibat Paparan Pestisida - Sarafina, Nur Nabilah; Aina, Ganea Qorry; Rica, Fitri Nur (Universitas Malahayati, 2023)
ABSTRACT Excessive use of pesticides may be an indicator that cholinesterase activity has decreased. Cholinesterase is an enzyme in body tissues that plays a role so that muscles, glands and nerve cells work regularly. Based on the results of blood cholinesterase monitoring of 347 agricultural workers in Central Java found 23.64% of workers with moderate poisoning and 35.73 with severe poisoning. This study aims to determine the blood cholinesterase levels of oil palm farmers exposed to pesticides and determine the mean, median and range of the examination of cholinesterase levels. This research was conducted in the oil palm plantation in Kedang Ipil village and for the examination of cholinesterase levels was carried out at the Kumala Clinic in Samarinda City. This research uses descriptive method. The samples used in this study were blood specimens from oil palm farmers exposed to pesticides. The results of the study obtained cholinesterase levels that meet normal values as many as 19 farmers and for abnormal cholinesterase levels as many as 1 farmer and obtained the value of the cholinesterase examination with an average of 7524 U / L, the median value of 7275 U / L and the range of 4859-9882 U / L. The conclusion of the research conducted on 20 samples is the value of cholinesterase levels in farmers exposed to pesticides 1-3 times / week with an age range of 21-70 years and a working period of 2-15 years in Kedang Ipil village is almost entirely normal there is only 1 farmer with abnormal cholinesterase levels. Keywords: Farmers, Pesticides, Cholinesterase ABSTRAK Penggunaan pestisida yang berlebihan dapat menjadi indikator penyebab turunnya aktivitas cholinesterase. Cholinesterase adalah enzim yang ditemukan dalam jaringan hewan yang membantu menjaga fungsi normal otot rangka, kelenjar, dan sel saraf tubuh. Ada 347 buruh tani di Jawa Tengah dimonitor kadar cholinesterase darahnya, dan didapatkan 23,64% keracunan ringan dan 35,73 keracunan berat. Riset ini bertujuan untuk menghitung rerata, median, dan rentang kadar cholinesterase darah pada petani kelapa sawit yang terpapar pestisida. Riset ini dilakukan di perkebunan kelapa sawit di kota Kedang Ipil dan dianalisis kadar cholinesterase di Klinik Kumala di kota Samarinda. Pendekatan deskriptif digunakan dalam riset ini. Sampel darah dikumpulkan dari produsen kelapa sawit yang terpapar pestisida untuk penyelidikan ini. Hasil penelitian didapatkan kadar cholinesterase yang memenuhi nilai normal ada 19 petani dan untuk kadar cholinesterase tidak normal ada 1 petani dan diperoleh nilai dari pemeriksaan cholinesterase dengan rata-rata yaitu 7524 U/L, nilai tengah 7275 U/L dan rentang yaitu 4859-9882 U/L. Kesimpulan dari penelitian yang dilakukan pada 20 sampel adalah nilai kadar cholinesterase pada petani yang terpapar pestisida 1-3 kali/minggu dengan rentang usia 21-70 tahun dan masa kerja 2-15 tahun didesa Kedang Ipil adalah hampir seluruhnya normal hanya terdapat 1 petani dengan kadar cholinesterase tidak normal. Kata Kunci: Petani, Pestisida, Cholinesterase